(untitled) (Cardiovascular Journal, 2019)
Background: Current cardioplegic technique during conventional coronary artery bypass grafting (CABG) does not consistently avoid myocardial ischemic damage in high risk patients. Alternatively revascularization without CPB is not always technically feasible. The on-pump beating technique eliminates global myocardial ischemia and thus reduce the mortality and morbidity in high risk patients. This study evaluates the early surgical outcomes of on-pump beating-heart CABG in comparison to conventional CABG. Methods: In this prospective study 60 high risk patients with EURO-SCORE of 6 and above were prospectively allocated into two groups in non-randomized way. Among them 30 patients underwent on-pump beating-heart CABG and 30 patients underwent conventional CABG. The early surgical clinical outcomes were compared between the groups. Results: On-pump beating heart CABG significantly reduced the duration of operation time, cardiopulmonary bypass time, postoperative ventilation time and intensive care unit (ICU) stay. Total blood loss and transfusion requirement were less with reduced Peak Creatine-Kinase level in On-pump beating heart CABG. 30 day mortality was less in On-pump beating heart CABG group (6.7% versus 13.3%). No significant differences between the groups were found in morbidity regarding stroke, renal failure, mediastinitis and atrial arrhythmia. Conclusion: On-pump beating heart CABG can be performed safely in high risk patients. It is still associated with the detrimental effect of CPB but eliminates intra-operative global myocardial ischemia. Cardiovasc. j. 2019; 12(1): 13-19